The Influence Of Baby Massage On Baby Sleep Quality In 3-4 Months In Bpm Pera Simalingkar B Medan In 2018 - Suyatni S, Endang; Munthe, Juliana; Sarah, Widia (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Baby massage is a fun way to relieve tension and feelings of anxiety, especially in babies, gentle massage will help relax the muscles so that the baby becomes calm and sleeps soundly. Data from BPM PERA Simalingkar B in 2018, out of 30 babies, 22 babies reported having trouble sleeping so they experienced quality sleep. The research objective was to determine the effect of infant massage on sleep quality for infants aged 3-4 months at BPM PERA Simalingkar B Medan in 2018. This type of research is a quasi experiment with one group pre test and post test design carried out in May and August 2018. There were 30 mothers of babies aged 3-4 months who visited and all of them were used as research samples. Collection using a questionnaire and analyzed using the Wilcoxon test at the limit of significance α = 0.05. The results showed that the quality of sleep for babies aged 3-4 months before the baby massage was good, namely 17 people (56.7%) and the rest, the quality of sleep was poor, namely 13 people (43.3%) and after the baby massage the quality of sleep was good to 24 people (80%) and the rest had poor sleep quality, namely 6 people (20%). There is an effect of massage for babies aged 0-6 months on the quality of sleep for babies before and after massage (p value 0.017 <0.05). It is recommended that the clinic leadership provide health education about baby massage to new mothers or mothers of babies who come to visit about baby massage and suggest doing massage so that the baby has good quality sleep. Health workers can provide brochures and leaflets about the correct technique and method of infant massage as a source of health information.